2014
DOI: 10.4269/ajtmh.13-0254
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidiosis in HIV/AIDS Patients in Kenya: Clinical Features, Epidemiology, Molecular Characterization and Antibody Responses

Abstract: Abstract. We investigated the epidemiological and clinical features of cryptosporidiosis, the molecular characteristics of infecting species and serum antibody responses to three Cryptosporidium-specific antigens in human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS) patients in Kenya. Cryptosporidium was the most prevalent enteric pathogen and was identified in 56 of 164 (34%) of HIV/AIDS patients, including 25 of 70 (36%) with diarrhea and 31 of 94 (33%) without diarrhea. Diarrhea in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 72 publications
3
38
0
Order By: Relevance
“…However, it is also likely that the association between anti- Cryptosporidium antibody responses and disease may reflect underlying cell-mediated immune responses. We found that HIV-infected patients with asymptomatic cryptosporidiosis not only had higher circulating IgG and fecal IgA levels to Cryptosporidium antigens compared to patients with diarrhea, but these patients, on average, also had significantly higher CD4+ T cell counts (88)*, which is known to be more predictive of disease severity. Future studies should aim to distinguish between the correlative and causative effects of the humoral response during Cryptosporidium infection.…”
Section: Immune Responses To Cryptosporidiummentioning
confidence: 88%
See 1 more Smart Citation
“…However, it is also likely that the association between anti- Cryptosporidium antibody responses and disease may reflect underlying cell-mediated immune responses. We found that HIV-infected patients with asymptomatic cryptosporidiosis not only had higher circulating IgG and fecal IgA levels to Cryptosporidium antigens compared to patients with diarrhea, but these patients, on average, also had significantly higher CD4+ T cell counts (88)*, which is known to be more predictive of disease severity. Future studies should aim to distinguish between the correlative and causative effects of the humoral response during Cryptosporidium infection.…”
Section: Immune Responses To Cryptosporidiummentioning
confidence: 88%
“…Interestingly, several studies found that acute and asymptomatic cryptosporidiosis were associated with higher IgG, IgM and/or IgA responses to Cryptosporidium spp. antigens compared to persistent cryptosporidiosis (8688), suggesting that humoral immunity may play a role in limiting the length and severity of infection. However, it is also likely that the association between anti- Cryptosporidium antibody responses and disease may reflect underlying cell-mediated immune responses.…”
Section: Immune Responses To Cryptosporidiummentioning
confidence: 99%
“…Major stages of the Cryptosporidium life cycle including sporozoite, trophozoite, meront, macrogamont, microgamont, zygote, immature oocyst, and matured oocyst have been defined based on the pathological investigation of infected tissue 3,18,26,28 . However, many in vitro studies report on a failure to detect all life cycle stages or the detection of abnormalities at particular phases of the C. parvum life cycle 38, 39 .…”
Section: Monitoring Of C Parvum Life Cycle Stages In Colo-680n Cultumentioning
confidence: 99%
“…http://dx.doi.org/10.1101/134270 doi: bioRxiv preprint first posted online May. 4, 2017; 3 Cryptosporidiosis causes a significant number of deaths in children and immunocompromised individuals [1][2][3][4] . It is caused by species of the genus Cryptosporidium, in humans typically by C. parvum and C. hominis.…”
mentioning
confidence: 99%
“…The age group most commonly affected is children from 1 to 9 years old [3]. Cryptosporidium causes prolonged diarrhoea in HIV patients regardless of the age group [4]. Here we present a case of chronic diarrhoea in a four year old male child with Acquired Immune Deficiency Syndrome (AIDS) and mile stone delay.…”
Section: Introductionmentioning
confidence: 99%